LEO Mega-Constellations for 6G Global Coverage: Challenges and Opportunities - Xie, Haoran; Zhan, Yafeng; Zeng, Guanming; Pan, Xiaohan (IEEE access, 2021)
Mega-constellations have the potential for providing 6G Internet owing to the unique advantage of global coverage. However, current satellite technologies are not omnipotent. There are still many challenging problems that need to be solved for mega-constellations to support 6G, e.g., efficient resource allocation, gratifying mobility management, and large-scale full-time TT&C (tracking, telemetry, and command). This paper starts with a novel definition of LEO mega-constellations and a brief review regarding the current typical mega-constellations, discussing the development direction of the mega-constellation air interface. Then, the key technologies development status of satellite networks is illustrated and analyzed from five aspects: network protocol, multiple access, satellite handover, TT&C, and interference mitigation, especially their adaptability in mega-constellations for 6G global coverage. Finally, considering the features and requirements of 6G, future challenges for mega-constellations and some potential solutions are proposed.